Clubfoot patients' demographic profile and outcomes of using the ponseti method at three selected hospitals in Zimbabwe - Mudariki, Debra (My University, 2020)
Background: Clubfoot is the most common musculoskeletal congenital abnormality and the Ponseti method is regarded as the gold standard of treatment. It has proven to be affordable, simple, and effective in correcting this deformity, particularly in low resource settings similar to Zimbabwe. Aim: The aim of this study was to establish the demographic profile and outcomes of patients with clubfoot treated using the Ponseti method at 3 hospitals in Zimbabwe, as well as determine whether results obtained were similar to those from regional and international research. Methodology: A descriptive retrospective records review of patients with clubfoot treated between January 2013 and December 2015 at Parirenyatwa, Harare Central and Mutare Provincial Hospitals was conducted. The main outcome was the final Pirani score at the end of the corrective phase. Data was analysed using STATISTICA Version 13.5. Results: There were 310 participants, mostly male (64.2%), with the majority (79.7%) in the maintenance phase of treatment. A total of 88.3% of the were participants between zero and two years of age at initial presentation, and the median (IQR) age was 3months (0.15-11months). Clubfoot was mostly of idiopathic (90.5%) and bilateral (55.2%) presentation, with positive family history of the deformity reported in 14.5% of participants. Mean (SD)Pirani scores at initial assessment for the right and left feet were 3.92 (1.33) and 3.99 (1.25) respectively. The Mean (SD) number of casts applied before tenotomy was 7.14 (4.48) ranging from 0-26 casts, and 72.5% of the participants had a tenotomy done. The proportion of left and right feet that attained a Pirani score of one or less at the end of the corrective phase was 79.2% and 82.5% respectively. Relapse was reported for 42.6% of participants in braces. At time of data collection, as many as 73.6% of the participants had stopped attending the clinics. Conclusion: Clubfoot treated using the Ponseti method had a good outcome at the end of the corrective phase. The demographic profile of patients managed at the three clinics and their treatment outcomes were in line with literature findings. There is, however, evidence of poor compliance and a high loss to follow up during the bracing phase and these need to be addressed to improve long term results.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Science in Physiotherapy to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, 2020